2020
DOI: 10.1186/s12891-020-03759-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross-segment spinal plasma cell granuloma:a case report

Abstract: Background Plasma cell granuloma (PCG) is a rare non-neoplastic entity, with the precise etiology remaining unclear. Vertebra-affected spinal PCG has not been reported yet. This report presented a case with cross-segment spinal PCG in thoracolumbar region. Case presentation A 32-year-old male patient presented to the authors’ hospital since his health check-up results showed osteolytic lesions in the thoracolumbar spine. He felt asymptomatic throughout the course. Radiological examination revealed destructive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The authors found that job stress was significantly associated with an increased risk of musculoskeletal disorders, particularly in the neck, shoulders, and lower back. Lin et al (2020) examined the relationship between job stress and musculoskeletal pain among university faculty in Taiwan. The authors found that job stress was positively associated with musculoskeletal pain, particularly in the neck, shoulders, and lower back.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…The authors found that job stress was significantly associated with an increased risk of musculoskeletal disorders, particularly in the neck, shoulders, and lower back. Lin et al (2020) examined the relationship between job stress and musculoskeletal pain among university faculty in Taiwan. The authors found that job stress was positively associated with musculoskeletal pain, particularly in the neck, shoulders, and lower back.…”
Section: Cardiovascular Diseasementioning
confidence: 99%